Complexity Analysis at Design Stages of Service Oriented Architectures as a Measure of Reliability Risks - Sheikh, M.; Myers, Doug; Ortega-Sanchez, Cesar (IGI Global, 2010)
Tremendous growth in interest of Service oriented Architectures (SOA) triggers a substantial amount of research in its reliability assurances. To minimize the risks of these types of systems’ failure, it is a requirement to flag those components of SOA that are likely to have higher faults. Clearly, the degree of protection or prevention of faults mechanism is not same for all components. This chapter proposes the usage of metrics that are simply heuristics and are used to scan the system model and flag complex components where faults are more likely to take place. Thus the metric output is some priority or it is a measure of likelihood of faults in a component. This chapter then suggests the designers for possible changes in the design if there remains any risk(s) of degradation of desired functionalities.